Can agricultural credit scoring for microfinance institutions be implemented and improved by weather data? - Ulf Römer; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
[Purpose] In recent years, the application of credit scoring in urban microfinance institutions became popular, while rural microfinance institutions, which mainly lend to agricultural clients, are hesitating to adopt credit scoring. The present study aims to explore whether microfinance credit scoring models are suitable for agricultural clients, and if such models can be improved for agricultural clients by accounting for precipitation. [...]
Keywords: 330; Microfinance; Credit scoring; Agricultural credit; Precipitation